Long Term Strategy for the Integrated Development of Bundelkhand Region, Perspective Planning Division, State Planning Institute, U.P, Lucknow - Planning Commission (Planning Commission, 1983)
The need for regional planning for backward regions is often emphasised on the basis of equity and justice. It is necessary, however, to realise that the reduction in regional disparities and acceleration of the rate of growth are not conflicting but complementary to each other in the long run. To illustrate this point, suppose there are two regions viz. A and B of the economy . The region is developed and B is under-developed. In this context, it has to be appreciated that certain minimum infra-structure facilities are required for enabling a region to attain a growth generating capacity. It is implied, therefore that region B is not having this minimum. Now if the available investible resources are equally allocated between these two regions, the growth rate of region A would definitely be higher than B, loading to a relatively lesser growth rate of the economy. It may be noted-that this situation would be obtaining only in the short run.
Long Term Strategy for the Integrated Development of Bundelkhand Region
Government of Uttar Pradesh